2022
DOI: 10.1097/shk.0000000000001950
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Derived Extracellular Vesicles Are Sufficient to Induce Endothelial Dysfunction and Coagulopathy

Abstract: Introduction: Although a number of studies have demonstrated increased release of extracellular vesicles (EVs) and changes in their origin differentials after trauma, the biologic significance of EVs is not well understood. We hypothesized that EVs released after trauma/hemorrhagic shock (HS) contribute to endotheliopathy and coagulopathy. To test this hypothesis, adoptive transfer experiments were performed to determine whether EVs derived from severely injured patients in shock were sufficient to induce endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Supernatant from the BAL fluid was stored at −80°C for subsequent testing. Total protein in the BAL fluid was measured with the BCA Protein Assay (Thermo Fisher Scientific, Waltham, MA) as an indicator of permeability 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supernatant from the BAL fluid was stored at −80°C for subsequent testing. Total protein in the BAL fluid was measured with the BCA Protein Assay (Thermo Fisher Scientific, Waltham, MA) as an indicator of permeability 21 …”
Section: Methodsmentioning
confidence: 99%
“…Total protein in the BAL fluid was measured with the BCA Protein Assay (Thermo Fisher Scientific, Waltham, MA) as an indicator of permeability. 21…”
Section: Lung Permeabilitymentioning
confidence: 99%
“…When EVs were isolated from severely injured patients and injected into naive mice, EC injury, as demonstrated by syndecan-1 shedding; coagulopathy; and organ injury were all significantly increased as compared with mice receiving EVs from minimally injured patients. 84 Similarly, Dyer et al 85 found that platelet EVs released after trauma were prohemostatic but also prothrombotic and contributed to enhanced venous thrombosis.…”
Section: Targeting Adamts-13 and Vwfmentioning
confidence: 98%
“…92,93 Activated endothelial cells also release EVs in response to various stimuli, including injury. 94 These EVs carry bioactive molecules such as TF, microribonucleic acids, and cytokines, which can contribute to coagulation and inflammation by further enhancing platelet activation, promoting leukocyte adhesion, and modulating immune cell function. 95 The net effect of inflammation and trauma-induced EV release on the coagulation status of the patient and their potential as a therapeutic to treat TIC is not fully understood and remains an area of ongoing investigation.…”
Section: Role Of Extracellular Vesicles In Mediating Sirsmentioning
confidence: 99%